The QIBB quality initiative of the vocational training system in Austria - Peachter, Manuela [Verfasser] (My University, 2010)
"The QIBB quality initiative was specifically developed for the vocational training system in Austria. The quality system is distinctive in that it includes both objectives and survey instruments designed to address the specific concerns of vocational training. There are general quality concepts and instruments that are common to all schools and others that are differentiated according to the type of school. The various school types within the vocational training system use QIBB first of all to conduct system-related surveys, for example to test common quality objectives in connection with national priorities. QIBB also enables schools to conduct internal evaluations. Survey instruments and an automatic evaluation are available from an online database. The test power of the survey instruments made available in QIBB are also verified in empirical analyses. Initial studies indicate that the test power of almost all survey instruments examined is satisfactory." (Autorenreferat, BIBB-Doku)
Keywords: S 3.1 Berufsbildende Schulen; L 6.2 Qualitätsmanagement/Qualitätssicherung; I 2.2.1 Westeuropa; Berufsbildung; Qualitätssicherung; Berufsbildendes Schulwesen; Österreich